Multivariate analysis and multitrait genotype-ideotype distance index (MGIDI) for selection of promising genotypes under drought stress in post rainy sorghum (Sorghum bicolor L. Moench) - R. Karthik1* and N. G. Hanamaratti2 (Electronic Journal of Plant Breeding)
The primary impediment to sorghum productivity in rabi conditions worldwide is drought. This study aimed to identify drought-tolerant lines from a germplasm set of 156 accessions which includes the elite breeding lines from institutes all over India using drought tolerance indices. Study was conducted during the rabi 2022-23 season at AICRP on Sorghum, University of Agricultural Sciences, Dharwad. Results indicated a significant reduction in mean yield under moisture stress conditions. Principal component analysis (PCA) and correlation analysis revealed a significant positive correlation between yield under stress (YS ) and indices such as the stress tolerance index (STI), geometric mean productivity (GMP), mean productivity (MP), mean relative performance (MRP), harmonic mean (HM), and yield index (YI), validating their effectiveness in selecting drought-tolerant genotypes. Cluster analysis sorted the germplasms into five clusters, differentiating tolerant and susceptible lines. Additionally, MGIDI analysis pinpointed lines G72, G78, G4, G100, and G135 as the most drought-tolerant based on multiple indices and yield under stress, suggesting their potential as valuable pre-breeding material for future breeding programs aimed at improving drought resilience in sorghum.